Lost Data and Transmition Speed Analysis on Incubator Analyzer Based IoT Technology - I Kade Nova Paramartha; Torib Hamzah; Bedjo Utomo; Sari Luthfiyah; Emre ÖZDEMĐRCĐ (International Journal of Advanced Health Science and Technology, 2022)
The importance of the readiness of the baby incubator for critical infant patients who are treated intensively encourages health technicians to carry out regular maintenance and calibration to overcome the problem of equipment malfunctions. Critical infant patients are babies who are treated in the NICU (Neonatal Intensive Care Unit) due to premature birth or babies using incubators are diagnosed with abnormalities or diseases, this situation makes babies need tools for survival, especially in the first month. Calibrating temperature control is very necessary for the incubator. In addition to temperature, it is necessary to control humidity so that the baby's respiratory system is in optimal condition. In addition, it is also equipped with a noise sensor to ensure that the noise in the baby incubator room is appropriate. From the above problems, a tool for temperature testing was made using a DHT22 sensor with five measurement points, humidity with a level of 30% RH - 60% RH and noise with a range of 30dB-60db to ensure the tool functions properly equipped with a lost data testing system and delivery speed. using internet access with thingspeak display. This research resulted in the design of a calibration tool with three parameters, namely the temperature setting at 33ºC the smallest error percentage is 0% and the largest error is 0.96%, and at the temperature setting 35ºC the smallest error percentage is 0.28% and the largest error is 4 .1%, humidity with an error percentage of 0.82% and noise with an error percentage of 0.93%. The drawback in using the Thingspeak application is that there is a limit on the channel ID, which can only display 8 readings, while the minimum time lag is 20 seconds. For the MAX4466 noise sensor, there are shortcomings, namely the accuracy in readings is not good.